Reflecting on chiral chimeric cancer and microbes: ambidextrous metabolism—the real danger? - Uzoigwe, Chika Edward (Frontiers in Cell and Developmental Biology, 2025)
The advent of genetic technologies requires consideration of neo-microbes. Attention must first be given to mirror life-forms that exhibit chirality discordant to that prevalent in nature. It is important to understand the merits and challenges faced by “contra-lateralized” organisms. The hypothesis here is that such organisms would suffer almost insuperable disadvantages. Their energy transduction mechanisms would result in ATP hydrolysis. They would be vulnerable to both innate achiral and acquired bi-chiral host immunity, but their defense and virulence mechanisms would exhibit heterodox chirality and thus be ineffectual. They would be savagely out-competed by commensals. It is hypothesized that the greatest utility and threat is from “ambidextrous” species that exhibit chiral chimerism/chiral duality. Different functions would be executed by effectors of varying chirality which may be inducible or facultative. Such microbiota would show predominantly conventional biochemical “lateralization”. However, few strategic functions would exhibit non-conformative chirality. One of the most significant dangers and potential benefits is the sheer unpredictability of the host response to counter-chiral antigens/molecules. Some synthetic enantiomers are an order of magnitude more active than their stereoisomer. Exceptional hazards thus lie in chiral chimeras that may elicit a hyper-exuberant immune reaction and shield themselves from that immune response by deploying a “cloaking” device in the form of a contra-chiral cell wall. As proof of this principle, cancer, which frequently overwhelms hosts, shows biochemical ambidexterity with bio-affinity for both L-glucose and D-glucose uptake and potentially also exploits D-amino acids for protein synthesis. Intriguingly, organisms of varying sophistication exhibit varying degrees of chiral duality. Hetero-chiral D-alanine and L-galactose derivates (fucose) and conjugate enzymes, for example, are bio-molecular protagonists. Extreme caution is required with such stereo-diverse agents, especially given that their chiral plasticity would be transmissible via plasmids or recombination, unlike obligate “mirror” species. However, effective regulation is fraught with obstacles as non-canonical chiral and bi-chiral enzymes and molecules already exist in nature, serving roles germane to species’ survival. The fundamental question is whether there is a need for a critical threshold for the heterochiral metabolic enrichment of organisms beyond which a tangible hazard subsists.